Building Good Family Time Management for Housewives in an Effort to Improve Family Economy - Putri Mauliza; Zahara Meutia (Abdimas Paspama, 2025)
This community service aims to analyze how to build good time management for housewives. The implementation method used in this Community Service activity is by conducting face-to-face meetings with participants consisting of housewives. Providing training and discussions and conducting direct Q&A. The training uses lecture, discussion, and Q&A methods. This aims to increase awareness and understanding of participants regarding the importance of building educational institutions that have competence and competitive advantages. While in the evaluation or assessment stage, participants will be given feedback on the community service program that has been implemented. In this case, it will be a consideration for the community service team in order to provide benefits for Sei Krio housewives. Based on the results of community service activities for housewives, suggestions are submitted, including: 1. More enthusiasm, especially for housewives so that the time they have can be used properly and effectively. 2. To continue to actively participate in training and competency development activities. 3. Community service activities like this can be carried out routinely both in the same location and in different locations to increase frugal behavior and a love of saving for children.